Unusual Conformation of a Dinuclear Paddle Wheel Copper(Ii) Complex. Synthesis, Structural Characterization and Epr Studies - Venegas-Yazigi, D; Venegas-Yazigi, D (2013)
An unusual and unique conformation of a paddle wheel type binuclear copper(II) complex containing acetate and acetamido ligands, {Cu 2(?2-O2CCH3)4} (OCNH2CH3) (1), was obtained by solvothermal synthesis. The structural characterization of this compound shows that the apical (acetamido) ligands are disposed at a 62 dihedral angle, generating a special conformation as a consequence of the synthetic method used. This conformation has not been reported in other paddle wheel copper(II) tetraacetate compounds. Electron paramagnetic resonance (EPR) spectra of powder samples of (1) were obtained at 9.5 and 33.8 GHz, while single crystal spectra were obtained at 33.8 GHz with a B0 applied in three orthogonal planes. The fit of the single crystal experimental data allowed gave gâ?¥ = 2.345 ± 0.003, and gâŠ¥ = 2.057 ± 0.005. The angular variation of the EPR line allows evaluation of the fine structure of (1), giving D = -0.337 ± 0.002 cm-1 and E = -0.005 ± 0.001 cm-1. The line width angular dependence, used together with the Anderson model and Kubo-Tomita theory, permitted the interdimer interaction to be evaluated as |J?| = (0.051 ± 0.002) cm-1. Using the powder spectral temperature dependence it was possible to evaluate the intradinuclear exchange coupling constan J0 as -101 ± 2 cm-1, which is considerably lower than that reported for other analogous copper(II) tetraacetate paddle wheel compounds (CuII-PW), showing the remarkable effect of the conformation of the terminal ligands on the magnetic interaction. © 2013 American Chemical Society.